Risk management in construction – preventive measure to reduce theft and vandalism problem / Che Amirah Che Awang - Che Awang, Che Amirah (Faculty of Architecture, Planning and Surveying, 2015)
Vandalism and theft are important issues relating to the construction site. Incidents of vandalism and theft sometimes depending on the type of construction work and this varies between road and highway construction, housing construction , airport , dam structure , and also the construction of the stadium. Contractors always lose materials, tools and expensive equipment because theft and vandalism whether by site workers or criminals who recognize an easy opportunity. The total losses from vandalism and theft on construction sites have been increasing dramatically over the past decade. The objective of this study is to study the risk management in construction to investigate the causes and effect of theft and vandalism problem construction site, to carry out recommendation the preventive measure to reduce theft and vandalism problems occur at construction site. To achieve the objective of this study, interview was conducted to get more detail information about the theft and vandalism problem and also the risk management in construction site. Besides that the questionnaire also distributed to the person that in charge the construction site.